Calligraphy bible a complete guide to more than 100 essential projects and techniques - Grebenstein, Maryanne (Watson-Guptill, 2012)
Offers advice on materials, tools, and organizing a workspace; provides instructions, tips, and techniques for calligraphy; and examines the history of writing.-- Source other than Library of Congress.